Regulation of Viral Restriction by Post-Translational Modifications - Célia Chamontin; Guillaume Bossis; Sébastien Nisole; Nathalie J. Arhel; Ghizlane Maarifi (Viruses, 2021)
Intrinsic immunity is orchestrated by a wide range of host cellular proteins called restriction factors. They have the capacity to interfere with viral replication, and most of them are tightly regulated by interferons (IFNs). In addition, their regulation through post-translational modifications (PTMs) constitutes a major mechanism to shape their action positively or negatively. Following viral infection, restriction factor modification can be decisive. Palmitoylation of IFITM3, SUMOylation of MxA, SAMHD1 and TRIM5α or glycosylation of BST2 are some of those PTMs required for their antiviral activity. Nonetheless, for their benefit and by manipulating the PTMs machinery, viruses have evolved sophisticated mechanisms to counteract restriction factors. Indeed, many viral proteins evade restriction activity by inducing their ubiquitination and subsequent degradation. Studies on PTMs and their substrates are essential for the understanding of the antiviral defense mechanisms and provide a global vision of all possible regulations of the immune response at a given time and under specific infection conditions. Our aim was to provide an overview of current knowledge regarding the role of PTMs on restriction factors with an emphasis on their impact on viral replication.